Addition of Re‐Bonded Nucleophilic Ligands to Activated Alkynes: A Theoretical Rationalization. Issue 3 (8th January 2020) - Álvarez, Daniel; Díaz, Jesús; Menéndez, M. Isabel; López, Ramón
Abstract : Reactions between [Re(X)(CO)3 (bipy)] (X = OH, OMe, NH p Tol, PPh2 ; bipy = 2, 2'‐bipyridine) complexes and methyl propiolate (HMAD) are studied to rationalize the different products experimentally obtained. Three reaction patterns were found with a common and limiting initial attack of X to HMAD. Thus, the experimental selectivity depends on the kinetics and/or thermodynamics of the last reaction stages. For X = OH and NH p Tol an easy intramolecular attack of the X‐linked HMAD to a highly electrophilic CO ligand is followed by a hydrogen transposition to this CO, yielding very stable species ( C‐CCOH products). When X = OMe, the insertion of the X‐attached HMAD into the Re–OMe bond ( ins product) takes place due to the smallest barrier and the largest stability of the ins route. Finally, when X = PPh2 the ins route becomes restricted and the route for the coupling of the X‐attached HMAD with bipy ( C‐Cbipy product) wins over the one for the coupling with CO ( C‐CCO product) only due to the larger stability of the C‐Cbipy product. Abstract : Computations reveal that the YR ligand determines both the reaction pattern and the obtained product in the reaction between [Re(YR)(CO)3 (bipy)] complexes and activated alkynes. Since all patterns start with the same nucleophilic addition, the experimental selectivity is dictated by the kinetics and/or thermodynamics of the last stage of the reaction.